Association Between Daily Gadget Use and Anxiety Levels Among Indonesian Elementary School Children: A Cross-Sectional Study - Rinjani, Santi; Fauziah, Yani Annisa; Winasari Dewi (Journal of Applied Nursing and Health, 2026)
Background: Background: The use of digital gadgets among school-aged children has increased substantially and may contribute to psychological problems, particularly anxiety. However, empirical evidence examining the association between daily gadget use duration and anxiety levels among elementary school children in Indonesia remains limited. Therefore, this study aimed to examine the association between daily gadget use duration and anxiety levels among elementary school children in Garut, Indonesia using a cross-sectional design. Methods: This cross-sectional study was conducted among elementary school children aged 6–12 years in Garut, Indonesia. Participants were recruited using stratified random sampling. Inclusion criteria were students aged 6–12 years who consented to participate, while students with diagnosed neurological or psychiatric disorders were excluded. The independent variable was daily gadget use duration, and the dependent variable was anxiety level measured using the Spence Children’s Anxiety Scale (SCAS), which showed good reliability (Cronbach’s alpha = 0.938). Spearman correlation analysis was performed. This study adhered to the STROBE guidelines. Results: The median daily gadget use duration was 3.0 hours (IQR 2.0–4.0), and the median anxiety score was 51.0 (IQR 40.0–60.0), with a mean of 49.65 (SD 17.17). Spearman correlation analysis revealed a significant positive association between daily gadget use duration and anxiety level among elementary school children (r = 0.215, 95% CI 0.01–0.40, p = 0.040), indicating a weak but statistically significant correlation. This finding suggests that longer gadget use duration was associated with slightly higher anxiety levels among children. Conclusion: Higher daily gadget use duration was associated with increased anxiety levels among elementary school children. These findings underscore the importance of monitoring gadget use and implementing early mental health screening to identify anxiety symptoms. School-based and community-based interventions may help promote healthy digital habits and support child mental health, particularly in resource-limited settings.